Is two days of intermittent energy restriction per week a feasible weight loss approach in obese males? A randomised pilot study. Issue 1 (9th August 2017) - Conley, Marguerite; Le Fevre, Lauren; Haywood, Cilla; Proietto, Joseph
Abstract : Aim: The 5:2 diet (two non‐consecutive days of 2460 KJ (600 calories) and 5 days of ad libitum eating per week) is becoming increasingly popular. This pilot study aimed to determine whether the 5:2 diet can achieve ≥5% weight loss and greater improvements in weight and biochemical markers than a standard energy‐restricted diet (SERD) in obese male war veterans. Methods: A total of 24 participants were randomised to consume either the 5:2 diet or a SERD (2050 KJ (500 calorie) reduction per day) for 6 months. Weight, waist circumference (WC), fasting blood glucose, blood lipids, blood pressure and dietary intake were measured at baseline, 3 and 6 months by a blinded investigator. Results: After 6 months, participants in both groups significantly reduced body weight ( P = <0.001), WC ( P = <0.001) and systolic blood pressure ( P = 0.001). Mean weight loss was 5.3 ± 3.0 kg (5.5 ± 3.2%) for the 5:2 group and 5.5 ± 4.3 kg (5.4 ± 4.2%) for the SERD group. Mean WC reduction for the 5:2 group was 8.0 ± 4.5 and 6.4 ± 5.8 cm for the SERD group. There was no significant difference in the amount of weight loss or WC reduction between diet groups. There was no significant change in diastolic blood pressure, fasting blood glucose or blood lipids in either dietary group. Conclusions: Results suggest that the 5:2 diet is a successful but not superior weight loss approach in male war veterans when compared to a SERD. Future research is needed to determine the long‐term effectiveness of the 5:2 diet and its effectiveness in other population groups.